Closed loop motion planning and control for mobile robots in uncertain environments - Tanner, Herbert G.; Kumar, Vijay R.; Loizou, Savvas (My University, 2003)
In this paper we present an extension to the navigation function methodology [6], [7] to the case where unmodelled obstacles are introduced in the workspace. A feedback control law is derived, based on the navigation function built on the initial workspace. Global convergence and collision avoidance properties are established. The derived closed form control law is suitable for real time implementation. Collision avoidance and global convergence properties are verified through computer simulations.
Keywords: Problem solving; Mobile robots; Computer simulation